Gross Findings of Widespread Visceral Metastasis of Prostatic Adenocarcinoma With Neuroendocrine Features: A Case Report - David J. Habibian; Alexander E. Dao; Shauna Kumar; Jeffrey Schiff; Kaitlin E. Kosinski; Aaron E. Katz (Urology Case Reports, 2016)
Although prostate cancer is common in the western world and is associated with favorable overall survival, neuroendocrine prostate cancer is difficult to detect and is known to aggressively metastasize throughout the body. This subset of disease thus has a poor prognosis, and early detection and treatment of neuroendocrine prostate cancer may increase overall survival. We present a case of a now deceased 63 year old male with extensive epicardial, respiratory, hepato-bilary, adrenal, genitourinary, and osseous tissue metastasis.